HUBUNGAN ANTARA DUKUNGAN SOSIAL ORANGTUA DENGAN EFIKASI DIRI PADA PEMAIN FUTSAL PUTRI DI UNIVERSITAS DIPONEGORO SEMARANG - AULIA, MAHARANI CITRA; Indrawati, Endang Sri (Jurnal EMPATI, 2017)
The aims of this research is to determine the correlation between parental social supportÂ  with self efficacy on female futsal players at Diponegoro University of Semarang. The population of this research is female futsal players at Diponegoro University, with 105 people as sample selected using convenience sampling technique. The technique of collecting data uses Likert scale psychology that consist of two scales, which are social support of parents (40 items, Î± = 0,947) and self efficacy scale (39 items, Î± = 0,946). Data analysis uses simple regression analysis with the help of SPSS version 22.0. The result shows that there is a positive correlation between parental social support with self efficacy on female futsal players at Diponegoro University Semarang with correlation coefficient 0,396 and p = 0,000 (p <0,05). Correlation coefficient value indicates there is a positive correlation that significant, it means the more positive the parental social support, the higher self efficacy. The value of determination coefficient is 0.157, this value shows that parental social affect self efficacy in amount of 15.7%.Â Â